ANALYSIS OF FACTORS AFFECTING THE MANAGEMENT OF VILLAGE FUNDS IN THE ANGKAISERA DISTRICT OF YAPEN ISLANDS REGENCY - Andarias Patiran; Melyanus Bonsapia; Milcha Handayani Tammubua; Muhamad Yamin Noch; Victor Pattiasina (Journal of Economics Review (JOER), 2022)
This research investigates the factors influencing village fund management in the Angkaisera District of Yapen Islands Regency. The examination was administered to a sample of 73 participants. Purposive sampling was used as the sampling method. Live surveys were used to collect data. Multiple regression was used to empirically test hypotheses. The results indicated that planning has no positive or significant impact on the allocation of village funds. It indicates that the planning of sub-district and village development has not met the village's objectives, so the village's finances have not been optimally managed. In addition, the implementation has no significant positive impact on the management of village fund allocation. It indicates that there are still irregularities in the implementation, and based on the realization of village funds, the community is not receiving them properly. Furthermore, accountability has a positive and significant impact on the administration of village fund allocation. This indicates that accountability has become a crucial aspect that can be executed effectively so that there are no issues with managing village funds. In addition, human resource competence has a positive and substantial impact on the management of village fund allocation. If the village apparatus has knowledge and experience in managing village finances, accountability for village fund management will increase. The allocation of village funds is unaffected by supervision; consequently, a lack of oversight will not diminish the accountability of village fund management.